Persistent influence of maternal obesity on offspring health: Mechanisms from animal models and clinical studies. (5th November 2016) - Wankhade, Umesh D.; Thakali, Keshari M.; Shankar, Kartik
Abstract: The consequences of excessive maternal weight and adiposity at conception for the offspring are now well recognized. Maternal obesity increases the risk of overweight and obesity even in children born with appropriate-for-gestational age (AGA) birth weights. Studies in animal models have employed both caloric excess and manipulation of macronutrients (especially high-fat) to mimic hypercaloric intake present in obesity. Findings from these studies show transmission of susceptibility to obesity, metabolic dysfunction, alterations in glucose homeostasis, hepatic steatosis, skeletal muscle metabolism and neuroendocrine changes in the offspring. This review summarizes the essential literature in this area in both experimental and clinical domains and focuses on the translatable aspects of these experimental studies. Moreover this review highlights emerging mechanisms broadly explaining maternal obesity-associated developmental programming. The roles of early developmental alterations and placental adaptations are also reviewed. Increasing evidence also points to changes in the epigenome and other emerging mechanisms such as alterations in the microbiome that may contribute to persistent changes in the offspring. Finally, we examine potential interventions that have been employed in clinical cohorts. Highlights: Maternal obesity leads to programming of excessive weight and adiposity in the offspring. The placenta integrates information from both mother and baby and plays a role in programming. Maternal and paternal obesity status can cause epigenetic disruption in the offspring. In utero exposures play an important role in shaping the offspring microbiome. Lifestyle interventions early in pregnancy may mitigate the programming effects of maternal obesity.